Pre-trial detention in 20th and 21st Century Common Law and Civil Law Systems - Mourlon, Fabrice (Cambridge Scholars Publishing, 2014)
Pre-trial detention refers to the period when a person, after being arrested, is detained so as to determine the nature of the offences and the characterization of the charges. This notion is part and parcel of the legal proceedings of a criminal investigation and aims at striking a fragile balance between protecting the State and respecting individual freedoms. Lots of examples can be quoted to illustrate the various pre-trial detention modalities in common law and civil law traditions, including the duration of custody; custody rights; right to silence; right to the presence of a lawyer; modalities and control of pre-trial detention; and procedures in case of wrongful detention. This book makes an important contribution to the newly-researched topic of pre-trial detention from a theoretical and empirical point of view. Papers alternatively consider various issues: they analyse the philosophical principles and policies underlying pre-trial detention and look at the different forms it takes according to several countries; on a more technical and pragmatic level, they raise the question of the use of an appropriate terminology and the problem of translation that may arise from the differences between the studied legal systems. Finally, they consider the checks and balances mechanisms put in place to limit the negative effects of the measures restricting liberty. This volume contains a selection of contributions by academics specialized in law and comparative criminal procedure, political science, history, sociology, linguistics, and legal translation, and offers a comparative analysis of countries with differing legal traditions